Orofacial pain relief project: Report of physiotherapy and dental care in patients with temporomandibular dysfunction during the COVID-19 pandemic period - Amparo Cardoso, Anne Karoliny; Cardoso Sarcinelli, Carlos Henrique; Santuzzi, Cintia Helena; Araujo de Sousa, Dhandara; Mayrink Gonçalves Liberato, Fernanda (Guará Journal, 2023)
Introduction:  The  Relief  -  Orofacial  Pain  project  emerged  in  2019 with the purpose of meeting the demand of a very under-diagnosed,  disabling  health condition  that  lacks  specialized  treatment,  temporomandibular  disorders  (TMD).  The  physical  restriction  imposed  by  the  pandemic  suspended  face-to-face  calls, but teleservices were started to offer support to patients through guidance and management strategies to control TMD. Objective: Report the experience of the Relief project with tele-service  during  the  Pandemic.  Method:  Patients  were  screened  using an online form and, after a lottery, invited to the consulta-tion by video call on the Google Meet platform, as were patients who already participated in the face-to-face mode. Discussion: Five  patients were  in  follow-up  when  face-to-face  activities  were suspended and all continued online. During the isolation period, 38 consultations were performed, covering 16 patients. During the online sessions, we sought to encourage healthy ha-bits, coping with limiting beliefs, self-management of pain and cessation of parafunctional habits. Conclusions: The teleservi-ce was essential for the continuity of TMD treatment, since part of  the  treatment  consists  of  changing habits  and  lifestyle,  in  addition to proving useful in the day to day of the project even outside social isolation.
Keywords: Temporomandibular disorders; Telehealth; Multiprofessional; Health education; COVID-19